การสื่อสารในการฟื้นฟูสภาพจิตใจเด็กและเยาวชนในศูนย์ฝึกและอบรมเด็กและเยาวชน - ยุรนันท์ ตามกาล (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This research aimed to study communication that officers and relatives used with juvenile delinquents. It also examined perception of juvenile delinquents regarding nonverbal communication of these two groups of people in interacting with the youth. The atmosphere at the training centers had also been observed. This research had 3 groups of samples, which were officers, juvenile delinquents’s relatives and the juvenile delinquents themselves. The sample size was 366 young people while the in-depth interview used 20 samples in 4 training centers, which included Ban Karuna, Ban Mutita, Ban U-bekkha and Ban Pranee Juvenile Training Centers. (The first three centers were for boys while the last one was for girls). The data were analyzed using descriptive statistics (frequencies,mean,percent) and inferential statistics (T-Test, One way ANOVA, Chi-square). The findings were as follows: 1. The verbal types that the officers mostly used with juvenile delinquents were persuasion to stop recidivism, followed by supportive statements and the officers had less nonverbal communication particularly touching than relatives. 2. The verbal types that the relatives mostly used with juvenile delinquents were persuasion to stop recidivism, following by supportive statements. 3. The verbal types that juvenile delinquents mostly heard from both officers and relatives were persuasion to stop recidivism. In terms of non-verbal communication, they received touching from relatives more than the officers and they felt good with that kind of communication that they receive from both groups of people. 4. Communication atmosphere in juvenile training centers could be said to possess a sense of confinement and relaxation suitable for mental rehabilitation.